Regulatory Mechanisms of Cell Polyploidy in Insects - Ren, Dani; Song, Juan; Ni, Ming; Kang, Le; Guo, Wei (Frontiers in Cell and Developmental Biology, 2020)
Polyploidy cells undergo the endocycle to generate DNA amplification without cell division and have important biological functions in growth, development, reproduction, immune response, nutrient support and conferring resistance to DNA damage in animals. In this paper, we have specially summarized current research progresses in the regulatory mechanisms of cell polyploidy in insects. First, insect hormones including juvenile hormone and 20-hydroxyecdysone regulate the endocycle of variant cells in diverse insect species. Second, cells skip mitotic division in response to developmental programming and conditional stimuli such as wound healing, regeneration and aging. Third, the reported regulatory pathways of mitotic to endocycle switch (MES), including Notch, Hippo and JNK signaling pathways are summarized and constructed into genetic network. Thus, we think that the studies in crosstalk of hormones and their effects on canonical pathways will shed light on the mechanism of cell polyploidy and elucidate the evolutionary adaptions of MES through diverse insect species.